Zig-zags, maples, and "[t]he pitfalls of façade first design": inside University House on Bowen Street, Wellington - McCarthy, Christine (Architectural History Aotearoa, 2024)
This paper examines the design origins and interior of the now demolished University House (Prouse and Wilson, 1940‐41), also known as the University Senate Building and the University Grants Committee Building.